#TITLE_ALTERNATIVE# - Najib Fauzan (NIM S2888610), Muh
ABSTRACT: The need for passenger car unit (pcu) and saturation flow values which represent actual conditions at an inter-section has led to using the laptop computer in the field. The British Department of Transport has made available programs to measure the two parameters. Their reliablity for field use was assessed in the present research by comparing the results from a field-operated laptop computer with video-taped observations of the same traffic. Both programs were found to be reliable when installed and operated by trained technicians. The SATFLOW program was initially run with arbitrary pcu values: 2.50 for buses; 2.25 for trucks; and 0.60 for motorcycles. For the right lane of two lanes of a signal-controlled intersection approach in Bandung, the 6-second time-slice derived saturation flows were 1525 pcu/h (a=99 pcu/h) from video-taped observations, and 1551 pcu/h (a=120 pcu/h) from EPSON HX20 field observations. At =0.05, these values from 100 cycles of compared data Caere not significantly different. For the left lane, 84 cycles of compared data showed saturation flows from video-taped observations of 1553 pcu/h (a=258 pcu/h) and 1598 pcu/h (a=277 pcu/h) from the EPSON HX20. At 0.05 these were not significantly different. For determination of pcu values, the laptop computer program (PCU) was found to be generally reliable when field-operated results were compared statistically with video-taped observations of the same traffic. Comparison of five pairs of data sets for the right lane, comprising a total of 190 observations, indicated acceptance of the null hypothesis at level of significance 0.05 for four of the five data sets. For the left lane, seven data sets comprising a total of 221 individual pairs of observations all indicated acceptance of the null hypothesis. Further analysis for comparing pcu values from video-taped and EPSON HX20 observations, considering the entire data as entities and applying the non-parametric Sign Test, indicated no significant difference (at a=0.05, two-tail test). The best estimates of pcu values determined from field observations were: 1.66 for buses (1.90 for left lane); 1.42 for trucks; and 0.42 for motorcycles (0.62 for left lane). For the two lanes of traffic of the studied approach, the best estimate of saturation flow was 1800 pcu/h per lane. This came from synchronous regression with simultaneous determination of the pcu values: 1.77 for bus; 1.37 for truck; and 0.50 for motorcycle as the best estimates. Tests to assess the presence of extremely small headways showed that about 1 percent of all field observations